Quin Franciscan Friary, chancel, MacNamara tomb, upright - O'Donovan, Danielle (My University, 2008)
Upright of MacNamara Tomb, moulding, from centre, comprises: angle fillet flanked at either side by right-angled rebate, quadrant. The rear corners of the rectangular upright are chamfered.
MacNamara Tomb
Keywords: quadrant; Architecture, Gothic -- Ireland; Quin Abbey; Architecture, Franciscan; Funerary monuments; Late Medieval; fillets (moldings); roll moldings